2022
DOI: 10.5435/jaaos-d-21-00651
|View full text |Cite
|
Sign up to set email alerts
|

Total Joint Arthroplasty in Homeless Patients at an Urban Safety Net Hospital

Abstract: Introduction: Homelessness is a key social determinant of health, and the patient population has grown to over 580,000. Total joint arthroplasty (TJA) is an effective treatment of symptomatic end-stage osteoarthritis of the hip and knee and has been shown to improve health-related quality of life in the general population. However, the literature on the outcomes of TJA among homeless patients is limited. Methods: We retrospectively reviewed 442 patients who underwent primary, unilateral TJA between June 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In addition to multiple health impacts, being homeless, having obesity and an unqualified job can all interact to raise the risk and progression of osteoarthritis and needs to be addressed accordingly [51][52][53][54][55][56]. These social factors are not new, and may clearly induce an ongoing or unexpectedly high socioeconomic burden on many diagnosed as having osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to multiple health impacts, being homeless, having obesity and an unqualified job can all interact to raise the risk and progression of osteoarthritis and needs to be addressed accordingly [51][52][53][54][55][56]. These social factors are not new, and may clearly induce an ongoing or unexpectedly high socioeconomic burden on many diagnosed as having osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Total joint arthroplasty (TJA) is a successful treatment protocol for end-stage knee and hip osteoarthritis (OA). 9 Annually, more than 1 million people undergo TJA in the USA. 10 As the population ages, the demand for TJA surgery is expected to increase substantially in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Total joint arthroplasty (TJA) is a successful treatment protocol for end-stage knee and hip osteoarthritis (OA) 9. Annually, more than 1 million people undergo TJA in the USA 10.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bennett et al 15 described the challenges created by the lack of social and rehabilitative services available to homeless patients following joint replacement surgery. Looking at postoperative surgical outcomes in PEH, Niu et al, 16 in their small cohort study of patients undergoing arthroplasy, found no increased risk of readmission, revision, or joint infection. However, on a much larger analysis of outcomes of coronary artery bypass surgery in U.S. veterans, Chandra et al 17 found homelessness to be an independent predictor of 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%